(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
The purpose of the article is to study co-variation mechanisms between the head of a nominal constituent and its adjectival or pronominal dependent(s) in the Vedic nominal morphology. By analyzing in detail nominal and pronominal morphology, we shall determine which agreement classes are possible and which ones are not, and define which role is played by desinential morphemes in co-variation. Furthermore, we shall point out that head-dependent relation shows up different features in the different Indo-European languages. KEYWORDS: nominal heads, Vedic, nominal morphology, inflection, agreement